2010
DOI: 10.48550/arxiv.1012.0559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of vacuum polarization for the annihilation channel in a strong laser field

Abstract: We consider vacuum polarization effects in the one-photon annihilation channel within a kinetic description of the e − e + plasma produced from the vacuum in the focal spot of counter-propagating laser beams. This entails essential changes in the structure of the photon kinetic equation. We investigate the domain of large adiabaticity parameters γ ≫ 1 where the photon radiation turns out to be very small. A more thorough examination of the domain γ 1 needs separate investigation. However, an exploratory study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…This is in contrast to the case γ ≫ 1, where accounting for multiphoton processes in the phase (44) leads to a constant component[45].…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…This is in contrast to the case γ ≫ 1, where accounting for multiphoton processes in the phase (44) leads to a constant component[45].…”
mentioning
confidence: 73%
“…The value f (0) can be estimated as a result of the numerical solution of the KE ( 16), ( 17) for e − e + excitations in a laser field [45]. For the PW laser system Astra Gemini we have E 0 ∼ 10 −5 E c , λ = 800 nm and f2 (0) ∼ 10 −11 [20,30].…”
Section: B Multiphoton Domain (γ ≫ 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the works [10,11] it was shown that the spectrum of the secondary photons in the low frequency domain k ≪ m has the character of the flicker noise. In the work [13] the inclusion of vacuum polarization effects in the one-photon radiation spectrum led to an essential change of the photon KE which was investigated in a broad spectral band including the annihilation domain ν ∼ 2m. First we have considered the domain of large adiabaticity parameters γ ≫ 1, where the photon radiation from the focal spot turns out to be very small.…”
Section: Introductionmentioning
confidence: 99%
“…This is then investigated for a variety of realistic optical and XFEL beam parameters. For related recent investigations see [10,11].…”
mentioning
confidence: 99%